Filogenia e taxonomia dos gêneros de Hadrotarsinae (Araneae: Theridiidae) - Barbara Teixeira Faleiro (2015)
This study proposes a phylogeny for the genera of the spider subfamily Hadrotarsinae based on the cladistic analysis of 69 morphological characters. The analysis includes 42 hadrotarsines of eight genera (Dipoena, Dipoenata, Emertonella, Euryopis, Guaraniella, Lasaeola, Phycosoma e Yaginumena), plus an outgoup composed by representatives of the the remaining theridiid subfamilies (Spintharinae, Latrodectinae, Pholcommatinae, Argyrodinae, Anelosiminae e Theridiinae). An analysis with equally weighted characters found 96 most parsimonious trees, whereas analyses with implied weighting and different concavity values (k = 1-6) always resulted in a single most parsimonious tree, although with different topologies. In all analyses, the monophyly of Hadrotarsinae is strongly supported, however, all the analyses failed to recover the monophyly of any genera of the subfamily. Only two clades were strongly supported (Phycosoma and Guaraniella+Dipoena granulata), the last one led to the proposal of the new combination Guaraniella granulata. A clade with most of the Neotropical species of Dipoena and other with the species of Yaginumena have low support values. The strict consensus of the trees based on equal weights analysis has a large basal polytomy in Hadrotarsinae. A clade composed by species of Euryopis and Emertonella emerged from all the implied weighting analyses and, despite the low support for this cade, a synonymy of these genera is proposed. The species of Lasaeola are never united in a single clade and their positions depend on weighting intensity. The same occurred for the Dipoenata species. Although there are some cohesive groups (Phycosoma, Guaraniella and Yaginumena), the problematic groups, particularly Dipoena, in which members have several different evolutionary histories, contribute to low phylogenetic resolution within the subfamily.